Social information changes the brain - Fernald, Russell D. (National Academy of Sciences, 2012)
Social animals live in complex physical and social environments requiring them to attend and rapidly respond to social and environmental information by changing their behavior. A key social influence is rank or status, a ubiquitous element in animal societies. Rank typically regulates access to reproduction and other resources, among other consequences for individuals. Because reproduction is arguably the most important event in any animals’ life, understanding how reproduction is regulated by social status and related physiological factors can instruct our understanding of evolutionary change. This article reviews evidence from a model social system in which reproduction is tightly controlled by social status. Surprisingly, changes in social status have rapid and profound effects over very short time scales and radically alter overt behavior, as well as physiological, cellular, and molecular factors that regulate reproductive capacity.